Ke Arah Studi "Etno-Media" - Akhmad Zaini Abar (Jurnal Ilmu Sosial dan Ilmu Politik, 2000)
Mass media become a subject in itself and hence deserve a treatment more than just instrument for communicating This article offers etno-media a new sub-field of media studies.